THE EFFECT OF THE GRAIN SIZE AND THE TYPE OF FLUIDS FILLING THE PORE OF IRON SAND TOWARD ITS MAGNETIC SUSCEPTIBILITY - Sangaji Hasmi Maharani Ipa (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2015)
This study was aimed at assessing the effect of grain size and type of ﬂ uid ﬁ lling the pore to its magnetic susceptibility value. Iron sand was separated based on the grain size into 0.5 mm, 0.25 mm, 0.125 mm and 0.074 mm and based on the condition; namely dry, mixed with distilled water and salt water. Some measurements were done in the laboratory using Bartington MS2 Susceptibility Magnetic Meter and XRD (X-Ray Diffraction). Bartington MS2 Susceptibility Magnetic Meter is used to measure the magnetic susceptibility of each grain size in all conditions, while XRD is used to identify the type and the concentration of minerals contained in each size of iron sand. Iron sand with the smaller grain size and high concentration of magnetite mineral will increase the value of magnetic susceptibility and its density. In addition, the type of ﬂ uids that ﬁ lls the pore of each size also gives the variations of the magnetic susceptibility.